Slow divergence integrals in generalized Liénard equations near centers - Renato Huzak; Peter De Maesschalck (Electronic Journal of Qualitative Theory of Differential Equations, 2014)
Using techniques from singular perturbations we show that for any $n\ge 6$ and $m\ge 2$ there are Liénard equations $\{\dot{x}=y-F(x),\ \dot{y}=G(x)\}$, with $F$ a polynomial of degree $n$ and $G$ a polynomial of degree $m$, having at least $2[\frac{n-2}{2}]+[\frac{m}{2}]$ hyperbolic limit cycles, where $[\cdot]$ denotes "the greatest integer equal or below".